Decentralized Control of DC Microgrids Using Interconnection and Damping Assignment Passivity-Based Control Technique: Experimental Verification - Mohammad Afkar; Cong Yuan; Roghayeh Gavagsaz-Ghoachani; Wiset Saksiri; Matheepot Phattanasak; Jean-Philippe Martin; Serge Pierfederici (IEEE Access)
A decentralized control approach is introduced in this paper that utilizes passivity-based control for two DC-distributed energy sources supplying the power of a load. Considering the concept of passivity, if each distributed generator exhibits passivity, this property will be maintained when these generators are connected in series or parallel. Thus, the stability of the entire system is guaranteed through the implementation of an interconnection and damping assignment passivity-based control (IDA-PBC). Additionally, droop voltage control is employed to achieve current sharing among the two power sources. If the model used is not an accurate representation of the original system, the controlled system may experience steady-state errors. To address these modeling errors, a compensation term is employed as the desired output voltage. The effectiveness of the proposed methodology is confirmed via results from simulation in three cases in which the performance of the system is investigated in start-up and load resistance or nominal load current change. With PBC, the system maintains stable operation. Experimental results validate the simulation results. Moreover, the proposed method guarantees global stability without knowing the parameters to prove global stability with local control.